PENDIDIKAN KELUARGA DALAM PRESPEKTIF AL- QUR’AN - Wahyudisyah, Taufiq; Kadar Yusuf (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The family is the first and foremost educational institution in Islam, playing a strategic role in shaping the faith, morals, and character of the next generation. However, modern social dynamics indicate a shift in values ​​and a weakening of the family's educational function, necessitating a reconstruction of the concept of family education based on the Qur'an. This study aims to analyze the concept of family trilogy in the Qur'an, examine the role and function of parents in children's education, and formulate the stages of children's education from a Qur'anic perspective. This study is a qualitative study with a library research type and uses a thematic interpretation approach (maudhu'i). The primary data source is the Qur'an, while secondary data are obtained from classical and contemporary commentaries and Islamic education literature. The analysis technique is descriptive-analytical by collecting verses related to the family, examining their linguistic and contextual meanings, and then synthesizing them within the framework of Islamic education. The results of the study indicate that family education in the Qur'an is built on three main dimensions (trimology): the family as an institution of sakinah (spiritual-psychological foundation), the family as a center of tarbiyah (internalization of monotheism and morals), and the family as a guardian of morals and continuity of generations. The role of parents includes the function as murabbi, role models (uswah), protectors, as well as motivators and facilitators of child development. The stages of child education take place gradually from pre-birth to puberty with an adaptive approach according to psychological development. This study confirms that the concept of family education in the Qur'an is integrative, systematic, and relevant to the development of contemporary Islamic education.